ANALISIS STRATEGI PEMASARAN UNTUK MENINGKATKAN DAYA SAING PADA USAHA MIKRO UD. AL MUBAROKAH PARE - Hariyono, Dava Fadilah; Dyah P, Ismayantika; Ayu Paramitha, Dyah (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
This study aims to determine the marketing strategy carried out by UD. AL Mubarokah Pare, inhibiting and supporting factors, and also designing superior marketing strategies to increase competitiveness. In this research the method used is qualitative by using descriptive research type aiming to gain a deep understanding of the situation at hand. The taking of informants was based on purposive sampling and the number of informants taken was 3 people. The results of this study indicate that the marketing strategy carried out by UD. AL Mubarokah Pare uses a marketing mix with the 4P technique (product, price, place, and promotion). Various products, affordable prices, strategic locations, and good promotions are the advantages of UD. AL Mubarokah in order to compete with similar businesses.